The effects of the War on the Syrian Agricultural Food Industry Potential - Mustafa Bayram; Yasemin Gök (Turkish Journal of Agriculture: Food Science and Technology)
Syria is a middle-income developing country with an economy that heavily depends on the food and agricultural sectors. However, with the recent Syria crisis/war, which started in March 2011, Syria’s food and agricultural industries have badly been affected. While the most of the processing factories and agricultural facilities such as industrial zones, food plants, greenhouses, irrigation canals and pumps have been damaged in the conflict areas, this resulted in a huge recession in the food and agricultural productivity of Syria. It is estimated that this will impact the country to meet the future food requirements as well. In this study, the agricultural and food potential of Syria was analysed based on agricultural area, available lands, irrigation, food sectors etc. for the future planning food policies.